Indonesia's Regulation Model as A Harmonization of Arrangements And Implementation Of Heirs' Approval On Asset Grants - Putri Purbasari Raharningtyas Marditi; Beatric Fortunata; Jefrianus Raga Koten (International Journal of Business, Economics, and Social Development, 2023)
Provisions on grants are regulated in Article 1666 of the Civil Code (BW), that grants are gifts by someone to another person free of charge and cannot be withdrawn, for movable goods (in front of a notary) and immovable goods (with a deed of Land Deed Official – "PPAT") when the grantor is still alive. The provisions of the grant as referred to (1) The grantor must be an adult (Article 1677 of the Indonesian Civil Code); (2) A grant must be made with a notarial deed originally kept by a notary (Article 1682 of the Indonesian Civil Code); (3) A grant binds the donor or issues a consequence starting from the grant with firm words received by the grantee (Article 1683 of the Indonesian Civil Code). But on the other hand, there is a provision that grants must pay attention to the approval of the heirs and do not violate their absolute rights, as stated in Article 913 Indonesian Civil Code. If the process has been carried out and does not violate the absolute rights of the heirs, then the object of the grant is legally transferred to the recipient of the grant. However, the practice is often considered to violate the rights of heirs, so most notaries and PPATs ask for a letter or statement of their approval. This condition shows that the arrangement of grants and the distribution of inheritance does not reflect the legal ideals of legal certainty, benefit, and justice. So based on these conditions, it is necessary to have a regulatory model that can be used as a reference in the formulation of arrangements for granting and guaranteeing inheritance distribution according to the Legitieme Portie. The regulatory model referred to in this paper is in the form of formulating a regulatory pattern that provides a comprehensive picture of the harmonization of grant arrangements and guarantees for inheritance distribution according to the Legitieme Portie which can guarantee the implementation of inheritance according to the Legitieme Portie that does not limit property owners in implementing grants on property. To describe the regulatory model, the research method used is a normative juridical method based on a statutory and conceptual approach. With the aim of being able to comprehensively present a form of a continuous pattern of arrangements that will form a protection system to ensure the implementation.